Contribution of ultrasound in combination with chlorogenic acid against Salmonella enteritidis under biofilm and planktonic condition. (April 2022) - Sun, Jinyue; Sun, Zhilan; Wang, Debao; Liu, Fang; Wang, Daoying
Abstract: The antibacterial and antibiofilm mechanisms of ultrasound combined with chlorogenic acid treatment for Salmonella enteritidis under biofilm and planktonic condition were investigated. S. enteritidis under biofilm and planktonic cells were treated with ultrasound, chlorogenic acid, and their combination for 5, 10, 20, 30, and 60 min. Results showed that the combined treatments exhibited synergistic effects that inactivated the S. enteritidis biofilm and planktonic cells. The nucleic acids and ATP leakage and CLSM imagines showed that the combining chlorogenic acid and ultrasound treatment significantly increased the permeability of the S. enteritidis cell membrane. SEM indicated that the combining chlorogenic acid and ultrasound treatment quickly destroyed the integrity of the S. enteritidis cell membrane, and the activity of respiratory chain dehydrogenase sharply decreased. Additionally, the amounts of polysaccharides in the S. enteritidis biofilms significantly decreased after the combined treatments. Hence, the combining chlorogenic acid and ultrasound treatment have potential applications in food preservation. Highlights: Ultrasound (US) promoted the chlorogenic acid (CA) to penetrate into S. enteritidis cells. US combined with CA destroyed the integrity of cell membrane and caused the release of internal constituents. US combined with CA decreased the polysaccharide contents in biofilms. US combined with CA decreased the activities of RCD in S. enteritidis cells.